GAMBARAN PENGETAHUAN PERAWAT IGD TENTANG CODE BLUE SYSTEM DI BALAI BESAR KESEHATAN PARU MASYARAKAT (BBKPM) MAKASSAR: Description of Emergency Room Nurses' Knowledge Regarding the Code Blue System at the Community Lung Health Center (BBKPM) Makassar - Mardiana Mustafa; Heriansyah Heriansyah; Dyah Ekowatiningsih; Rauf Harmiady; Yulianto M (Media Keperawatan: Politeknik Kesehatan Makassar, 2025)
Background: Code Blue is a universal emergency management system designed to handle critical medical cases requiring immediate intervention, particularly cardiac arrest. This system was first implemented at Bethany Medical Center, Kansas, USA, and remains the only color code used globally for identical emergencies. In Indonesia, the general use of Code Blue was established in 2008 in alignment with healthcare service quality standards. Objective: This study aims to identify the level of nurses' knowledge regarding the Code Blue System in the Emergency Room (IGD) of the Lung Health Center (BBKPM) in Makassar. Methods: This study utilized a quantitative approach with a simple descriptive design. The sampling technique employed was total sampling, involving the entire population of nurses in the unit. Results: The results illustrate the nurses' knowledge regarding the Code Blue System at BBKPM Makassar. The data indicates that the knowledge level of nurses in the Emergency Room falls into the good category. Conclusion: It can be concluded that nurses in the BBKPM Emergency Room possess a good level of knowledge regarding the Code Blue System. However, the consistent implementation of this system within the hospital environment remains crucial to improving service quality and fostering a sense of safety for patients, especially in cardiac arrest cases. It is recommended that future researchers conduct more in-depth studies on this topic.   Keywords: Code Blue System, Knowledge Level, Nurses, Emergency Room, Emergency Care